Research on Envelope Profile of Lithium Niobate on Insulator Stepped-Mode Spot Size Converter - Jianfeng Bao; Dengcai Yang; Zhiyu Chen; Jingyuan Zhang; Feng Yang (Micromachines)
To enhance the end-face coupling efficiency of lithium niobate on insulator (LNOI) chips, in conjunction with current device fabrication processes, a stepped spot size converter (SSC) based on a special outer envelope profile has been proposed and investigated. This stepped SSC can reduce the coupling loss between the LNOI waveguide and a normal single-mode optical fiber. First, the output waveguide of a mode converter was proposed and simulated, in which the mode field had the biggest overlapping integral factor with a single-mode fiber (MDF ≈ 9.8 μm). Then, a stepped LNOI waveguide, the basic structure of the mode converter, with three kinds of outer envelope profile, was proposed and analyzed. Through analysis of the impacts of different envelope profiles on mode spot conversion efficiency, the relationship between envelope profile and propagation efficiency was obtained. Additionally, the rule of LNOI stair height variation tendency and the pattern of mode spot conversion efficiency for the multi-step mode spot converter in LNOI were obtained. Ultimately, a stepped SSC with a COS-shaped envelope curve was adopted. When this stepped SSC is coupled to single-mode fiber with a mode-field diameter of 9.8 μm, the coupling efficiency of the TE mode was 95.35% at the wavelength of 1550 nm.